Application of Peer Tutoring Method To Improve Dancing Skills in Class IV Traditional Dance Materials at SD 1 Pangenrejo - Muflikhul Khaq; Ade Ferliana Putri (research, training and philanthropy institution Natural Aceh, 2022)
Improving the quality of education is influenced by the factors involved such as teachers, curriculum, infrastructure and the environment. The curriculum for primary and secondary education is required to include art and culture subjects. The problem that is obtained at this time is the low interest of students in cultural arts subjects which results in the skills of students, especially traditional dancing, have not yet reached the criteria for completeness. Another problem is teacher-centered learning so that it limits students in exploring their skills. The purpose of this study was to improve students' traditional dancing skills with the specified Minimum Completeness Criteria, namely 80. The subjects in this study were 8th grade elementary school students. This is in accordance with the restrictions on activities during the COVID-19 pandemic. The instruments in this study were observation sheets, interview sheets, documentation, field notes and tests. This type of research is Classroom Action Research. The results showed that in the pre-cycle activities the average result was 50.78 which the value had not yet reached the KKM, then the first cycle was carried out for 4 meetings, each meeting took a score to find the average at the end of the cycle. Cycle I got an average score of 64.28. In cycle II, the researcher also held 4 meetings and got a final average score of 83.46 which the value has reached the specified KKM. students' traditional dance.